Optimization of process parameters for vacuum drying of ripe jackfruite bult (Artocarpus heterophyllus L.) - PADMAVATHI D; Dr. Santhi Mary Mathew (Guide) (Tavanur 2015 Department of Food and Agricultural Process Engineering)
Optimization of process parameters for vacuum drying of ripe jackfruite bult (Artocarpus heterophyllus L.)
Optimization of process parameters for vacuum drying of ripe jackfruite bult (Artocarpus heterophyllus L.)